Language and Culture in Multicultural Society of English Language Course: A Case Study of Sociolinguistics (NOBEL: Journal of Literature and Language Teaching, 2020)
This research tried to fulfill the gap in exploring how international tutors learn about the Indonesian language as well as to examine their personal perspectives on the influence of Indonesian culture towards its language. The qualitative descriptive method used as the research design since, in the analysis of the data, someone cannot truly learn about certain languages without learning about its culture and its society. Learning, knowing, and understanding about the local culture means that someone can practically easier teach language to its society. Overall, all international tutors feel fascinated by how Indonesian people think, speak, and act, which influenced by the culture of its society. They also conclude that Indonesian people are expressing and using their language based on their experience with their own culture.